Invader disruption of belowground plant mutualisms reduces carbon acquisition and alters allocation patterns in a native forest herb. Issue 2 (27th October 2015) - Hale, Alison N.; Lapointe, Line; Kalisz, Susan
Summary: Invasive plants impose novel selection pressures on naïve mutualistic interactions between native plants and their partners. As most plants critically rely on root fungal symbionts (RFSs) for soil resources, invaders that disrupt plant–RFS mutualisms can significantly depress native plant fitness. Here, we investigate the consequences of RFS mutualism disruption on native plant fitness in a glasshouse experiment with a forest invader that produces known anti‐fungal allelochemicals. Over 5 months, we regularly applied either green leaves of the allelopathic invader Alliaria petiolata, a nonsystemic fungicide to simulate A. petiolata 's effects, or green leaves of nonallelopathic Hesperis matronalis (control) to pots containing the native Maianthemum racemosum and its RFSs. We repeatedly measured M. racemosum physiology and harvested plants periodically to assess carbon allocation. Alliaria petiolata and fungicide treatment effects were indistinguishable: we observed inhibition of the RFS soil hyphal network and significant reductions in M. racemosum physiology (photosynthesis, transpiration and conductance) and allocation (carbon storage, root biomass and asexual reproduction) in both treatments relative to the control. Our findings suggest a general mechanistic hypothesis for local extinction of native species in ecosystems challenged by allelopathic invaders: RFS mutualism disruption drives carbon stress, subsequent declines in native plant vigor, and, if chronic, declines in RFS‐dependent species abundance. Abstract : See also the Commentary by Gilliam